Moon in the ground - Antill, Keith (Melbourne : Norstrilia Press, 1979)
Australian science fiction set around Pine Gap near Alice Springs.
Keywords: Art - Rock art - Painting; Religion - Dreaming; Literature and stories - Non indigenous - Fiction; Race relations - Representation - Literature; Northern Territory (NT); Kuyunba / Pine Gap (South Central NT SF53-14); Australia